Stochastic processes dominate the community assembly of ectomycorrhizal fungi associated with Betula platyphylla in Inner Mongolia, China - Min Li; Zhaoyun Meng; Jinyan Li; Xuan Zhang; Yonglong Wang; Xinyu Li; Yuze Yang; Yue Li; Xunjue Yang; Xiuli Chen; Yongjun Fan (PeerJ)
The maintenance and driving mechanisms of microbial community structure have become important research focuses in microbial ecology. Therefore, clarifying the assembly of ectomycorrhizal (EM) fungal communities can provide a relevant basis for studying forest diversity, ecological diversity, and ecological evolution. Betula platyphylla is a typical EM dependent tree species with characteristics such as renewal ability and strong competitive adaptability, and it plays a crucial ecological function in Inner Mongolia. However, the research on EM fungi’s diversity and community assembly is very limited. We investigated EM fungal communities associated with B. platyphylla from 15 rhizosphere soil samples across five sites in Inner Mongolia. The fungal rDNA ITS2 region was sequenced using Illumina Miseq sequencing. A total of 295 EM fungal OTUs belonging to two phyla, three classes, nine orders, 20 families, and 31 genera were identified, of which Russula, Cortinarius, and Sebacina were the most dominant taxa. Significant differences existed in the composition of dominant genera of EM fungi across the five sites, and the relative abundances of dominant genera also showed significant differences among the sites. The β NTI and NCM fitting analyses suggest that stochastic processes mainly determine the EM fungal community assembly. Our study indicates that B. platyphylla harbors a high EM fungal diversity and highlights the important role of the stochastic process in driving community assembly of mutualistic fungi associated with B. platyphylla in north China.